LEAF FLUSHING AS TAXONOMIC EVIDENCE OF SOME DIOSPYROS SPECIES - Eva Kristinawati Putri; Tatik Chikmawati (PTTI, 2015)
People tend to use generative structures for plant identification. Nevertheless, generative structure availibility limits the identification practice for a plant with once-a-year fruit-bearing phase, such as Diospyros L. (Ebenaceae). Being vegetative characters, leaf flushing are rarely used for plant identification so that they have not been explored as a taxonomic evidence. In this paper, leaf flushings and their taxonomic implication were studied using eight species of Diospyros grown in Ecopark of Cibinong Science Center LIPI, Bogor (West Java). Observations on morphological characters were undertaken on three twigs (which have three flushing sets and an apical dormant bud) taken from each 22 individual trees of Diospyros species available. Morphological development observation showed that bud rhythmic growth produce flushing sets usually distinguishable from the previous sets. Leaf flushing time after a period of dormancy and the presence of small reduced leaf in some species indicated anarrested growth in the bud. Leaf flushings can be found every few months or all year around with a period of 40–55 days for the formation of mature leaves. Leaf flushing provided 39 characters that can be used as taxonomic evidence for distinguishing the eight species of Diospyros observed. A determination key for these species solely based on leaf flushing characters is presented.